Connection Between Chromosomal Location and Function of CtrA Phosphorelay Genes in Alphaproteobacteria - Tomasch, Jürgen; Koppenhöfer, Sonja; Lang, Andrew S. (Frontiers in Microbiology, 2021)
Most bacterial chromosomes are circular, with replication starting at one origin (ori) and proceeding on both replichores towards the terminus (ter). Several studies have shown that the location of genes relative to ori and ter can have profound effects on regulatory networks and physiological processes. The CtrA phosphorelay is a gene regulatory system conserved in most alphaproteobacteria. It was first discovered in Caulobacter crescentus where it controls replication and division into a stalked and a motile cell in coordination with other factors. The locations of the ctrA gene and targets of this response regulator on the chromosome affect their expression through replication-induced DNA hemi-methylation and specific positioning along a CtrA activity gradient in the dividing cell, respectively. Here we asked to what extent the location of CtrA regulatory network genes might be conserved in the Alphaproteobacteria. We determined the locations of the CtrA phosphorelay and associated genes in closed genomes with unambiguously identifiable ori from members of five alphaproteobacterial orders. The location of the phosphorelay genes was the least conserved in the Rhodospirillales followed by the Sphingomonadales. In the Rhizobiales a trend towards certain chromosomal positions could be observed. Compared to the other orders, the CtrA phosphorelay genes were conserved closer to ori in the Caulobacterales. In contrast, the genes were highly conserved closer to ter in the Rhodobacterales. Our data suggest selection pressure results in differential positioning of CtrA phosphorelay and associated genes in alphaproteobacteria, particularly in the orders Rhodobacterales, Caulobacterales and Rhizobiales, that is worth deeper investigation.